ANALYSIS OF CONTENT OF β-CAROTEN COMPOUNDS IN PALM FRUIT (Arenga piñata) FROM BAUMATA VILLAGE - James Ngginak; Andriani Rafael; Djeffry Amalo; Sonya Titin Nge; Coni Sandra Bisilissin (Fakultas MIPA Universitas Negeri Gorontalo, 2020)
Society is now vulnerable to various diseases. people need to be educated in the selection of foods that are healthy and good for the body. β-carotene is a healthy food that is good for the body. The study was conducted to determine the content of β-carotene compounds in fruit (Arenga piñata). Samples were obtained from Baumata village. The study used Thin Layer Chromatography (TLC) and Spectrophotometry methods. The research data were analyzed according to linear regression equations and relevant reference studies. The results of the study using the TLC method showed that the Rf value for palm fruit was 0.943 and the Rf value for the standard β-carotene was 0.544. Spectrophotometric test showed the content of β-carotene compounds from palm fruit extract at a wavelength of 470 nm had a concentration of 26.18 ppm with absorbance of 0.055. As for the standard β-carotene concentration of 35.83 ppm with an absorbance value of 0.080. Based on the results of the study it can be concluded that the palm fruit (fro) contains β-carotene. The presence of β-carotene in palm fruit can be used as a healthy functional food choice for the community as well as a choice of sources of vitamin A.